PEMBUATAN COOKIES GLUTEN DAN SKILL BERWIRAUSAHA UNTUK MASYARAKAT PARANGJORO DAN MAHASISWA POLITEKNIK NEST SUKOHARJO - Safira, Safira; Hadi, Putra Pratomo; Aini, Rukmi Nur; Wati, Galuh Rachma; Dewi, Febriana Mulya (JANAKA : JURNAL PENGABDIAN MASYARAKAT KEWIRAUSAHAAN INDONESIA, 2024)
This community service activity aims to provide entrepreneurial skills to the Parangjoro community and Nest Polytechnic students for making healthy gluten-free and halal snacks for children. This community service activity was carried out in the Nest Polytechnic Sukoharjo kitchen lab. The results of this community service activity are that the participants understand how to make healthy snacks and then will be promoted to gain profit, so that it can be the basis for entrepreneurship Keywords: Cookies, Healthy Snacks, Entrepreneurship